Aldafermin in patients with non-alcoholic steatohepatitis (ALPINE 2/3): a randomised, double-blind, placebo-controlled, phase 2b trial. (July 2022) - Harrison, Stephen A; Abdelmalek, Manal F; Neff, Guy; Gunn, Nadege; Guy, Cynthia D; Alkhouri, Naim; Bashir, Mustafa R; Freilich, Bradley; Kohli, Anita; Khazanchi, Arun; Sheikh, Muhammad Y; Leibowitz, Mark; et al.
Summary: Background: Non-alcoholic steatohepatitis (NASH) is characterised by hepatic steatosis, inflammation, and injury, and is associated with an increased risk of liver transplantation and death. NASH affects more than 16 million people in the USA, and there is no approved therapy. The aim of this study was to evaluate the safety and efficacy of aldafermin, an engineered analogue of the gut hormone fibroblast growth factor 19 (FGF19). Methods: In this randomised, double-blind, placebo-controlled, phase 2b study (ALPINE 2/3) in patients with biopsy-confirmed NASH and stage 2 or 3 fibrosis, we randomly assigned patients stratified by fibrosis stage in a 1:1:1:1 ratio to receive placebo, aldafermin 0·3 mg, 1·0 mg, or 3·0 mg once daily for 24 weeks at 30 study sites in the USA. Patients, investigators, the funder, and all other staff, were masked to treatment assignment throughout the study. The primary endpoint was an improvement in liver fibrosis of at least one stage with no worsening of NASH at week 24. Analyses were done by intention-to-treat. This trial is registered with ClinicalTrials.gov, number NCT03912532, and has been completed. Findings: Between May 16, 2019, and Sept 4, 2020, 786 patients were screened, of whom 171 were randomly assigned to a treatment group and included in the intention-to-treat population: 43 in the 0·3 mg aldafermin group, 42 in the 1·0 mg group, 43 in the 3·0 mg group, and 43 in the placebo group. In total, 145 (85%) of patients completed treatment. At week 24, among patients with biopsies at both baseline and week 24, was seven (19%) of 36 patients in the placebo group, 11 (31%) of 36 in the 0·3 mg aldafermin group (difference 90% CI 12% [−9 to 33]; p=0·11), five (15%) of 34 patients in the 1·0 mg group (difference −5% [−24 to 13]; p=0·80), and 11 (30%) of 37 patients in the 3·0 mg group (difference 10% [−9 to 30]; p=0·12) had an improvement in liver fibrosis of at least one stage with no worsening of NASH, without meeting the prespecified significance for dose response (p=0·55). Adverse events were mostly mild or moderate in severity. Diarrhoea occurred in six (14%) of 43 patients in the placebo group, three (7%) of 43 patients in the 0·3 mg aldafermin group, five (12%) of 41 patients in the 1·0 mg group, and ten (23%) of 43 patients in the 3·0 mg group. Incidences of serious adverse events and discontinuations owing to adverse events were similar between groups. Interpretation: Aldafermin was generally well tolerated but did not produce a significant dose response on fibrosis improvement of at least one stage with no worsening of NASH, despite positive effects on a number of secondary endpoints. The findings of this trial may have implications for the design of future NASH trials. Funding: NGM Biopharmaceuticals.